2022
DOI: 10.1097/xcs.0000000000000118
|View full text |Cite
|
Sign up to set email alerts
|

State Gun Law Grades and Impact on Mass Shooting Event Incidence: An 8-Year Analysis

Abstract: BACKGROUND: Gun violence, particularly in the form of mass shooting events (MSE), is a growing, significant public health crisis in the US. Whether stricter gun laws decrease MSE is not known. We hypothesized that stronger state gun laws would be associated with lower MSE incidence. STUDY DESIGN: Mass shooting events, defined as at least 4 people injured in a single event, and state gun law grade data for years 2014 through 2021 were obtained from the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
5
1
Order By: Relevance
“…There was no discernible association noted in this study between gun laws and MSEs with other studies showing similar findings . However, this study looked at more than 4 years of MSEs during which gun laws varied in strength.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…There was no discernible association noted in this study between gun laws and MSEs with other studies showing similar findings . However, this study looked at more than 4 years of MSEs during which gun laws varied in strength.…”
Section: Discussioncontrasting
confidence: 64%
“…The overall effect of gun laws on MSE incidence is unclear. In the literature, some evidence shows that the strength of state gun law has no impact on MSE incidence while other studies have shown that tougher gun laws can result in decreased MSE incidence and number of fatalities . Overall, this represents a complex problem that requires further analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Public health education and training has endured rapid change over the years accompanied by many challenges that have shaped current public health paradigms, practices, and policies. Following the stilted response to the COVID-19 pandemic, we have yet to witness justice in racially motivated attacks against unarmed Black Americans (McCoy, 2020) and Asian Americans (Gover et al, 2020), the abrogation of sexual and reproductive rights (Hubler, 2022), and the institutional inaction on firearm control (Duchesne et al, 2022). Academic institutions of public health are expected to abide their training approaches by national standards and priorities of the Council on Education for Public Health (CEPH, 2021), while also striving to curate a diverse student collective.…”
mentioning
confidence: 99%